Health benefits of Moringa oleifera - Abdull Razis, Ahmad Faizal; Ibrahim, Muhammad Din; Kntayya, Saie Brindha (Asian Pacific Organization for Cancer Prevention and Control, 2014)
Phytomedicines are believed to have benefits over conventional drugs and are regaining interest in current research. Moringa oleifera is a multi-purpose herbal plant used as human food and an alternative for medicinal purposes worldwide. It has been identified by researchers as a plant with numerous health benefits including nutritional and medicinal advantages. Moringa oleifera contains essential amino acids, carotenoids in leaves, and components with nutraceutical properties, supporting the idea of using this plant as a nutritional supplement or constituent in food preparation. Some nutritional evaluation has been carried out in leaves and stems. An important factor that accounts for the medicinal uses of Moringa oleifera is its very wide range of vital antioxidants, antibiotics and nutrients including vitamins and minerals. Almost all parts from Moringa can be used ad a source for nutrition with other useful values. This mini-review elaborates on details of its health benefits.